Literature support to the Third World Studies Program of the College of Arts and Sciences, University of the Philippines - Martin, Ramon R. (1981)
This paper is more than a bibliographic compilation of literature available in the Third World Studies Program Reading Room of the College of Arts and Sciences, University of the Philippines. This is not a mere checklist of materials with annotations. This work exceeds its avowed aim and provides the reader with enlightening information about the Third World.